Pakistani University ESL Teachers and Students’ Perceptions Regarding Plagiarism - Farha Sadia Qureshi,; Muhammad Younus, (Al-Qanṭara, 2025)
The study aims to explore the perception of Pakistani ESL teachers and students regarding plagiarism at the university level in the Pakistani context. The study employed the mixed method approach to collect data from students and teachers by distributing questionnaires among students for quantitative data and by conducting interviews of teachers for qualitative data. Using the purposive sampling technique, a survey questionnaire was distributed among 332 ESL students of the BS English program at two private and two public sector universities in Karachi. The quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed by thematic analysis The analysis of students’ survey responses revealed that students’ commit plagiarism due to a lack of awareness about plagiarism, its types and consequences, limited language competency, and a lack of using critical thinking skills. They were also provided limited support from their teachers and university, and were unaware of university policy against plagiarism. The analysis of university teachers’ semi-structured interviews also confirmed that students are not aware of plagiarism and its types, and they commit it owing to a lack of language capability and critical approach in the process of learning. University teachers were aware of the concept of plagiarism, but had limited understanding of the types of plagiarism. They complained about the absence of plagiarism policy at undergraduate levels, limited or no access to plagiarism detection software, and lack of training and resources to combat plagiarism among the students.